Pemberhentian Sekretaris Desa Poncoharjo oleh Kepala Desa Berdasarkan UU No.6 Tahun 2014 (Studi Putusan No.62/G/2022/PTUN.SMG): The Dismissal of Poncoharjo Village Secretary by The Village Head Based on Law No.6 of 2014 (Study of Decision No.62/G/2022/PTUN.SMG) - Ananda Syauqi Febrian; Ferry Edwar (Reformasi Hukum Trisakti, 2024)
Villages are the lowest part of the government system in the government structure in Indonesia. The Village Government consists of the Village Head and Village Apparatus, which includes the Village Secretary, Regional Executive, and Technical Implementer. In carrying out his duties as Village Head, sometimes refers to authority, as happened in Poncoharjo Village, Demak Regency. The main problem is whether the termination of the Secretary of Poncoharjo Village, by the Village Head is in accordance with Law Number 6 of 2014 and what legal action was taken by the Secretary of Poncoharjo Village which was terminated by the Village Head. The type of research is normative legal research, descriptive in nature, using secondary data and primary data analyzed qualitatively, drawing conclusions using deductive logic. The results of the analysis of the termination of the Poncoharjo Village Secretary, Demak Regency by the village head were not in accordance with applicable regulations and in terms of terminating village officials, the Poncoharjo Village Head was not consulted regarding the decision. The legal action taken by the Secretary of Poncoharjo Village which was stopped by the Head of Poncoharjo Village, Demak Regency was through administrative efforts and filing a lawsuit with the PTUN.